Ticks and tick-borne pathogens in Finland: Studies on species distribution, pathogen prevalence, and historical Borrelia seroprevalence - Lamppu, Maija (fi=Turun yliopisto|en=University of Turku|, 2026)
Ticks and tick-borne diseases are an increasing public health concern in Finland and other Nordic countries, as cases of Lyme borreliosis (LB) and tick-borne encephalitis (TBE) continue to rise. A decade ago, tick research in Finland was still scarce, and the last nationwide study on tick distribution had been published in 1961. The aim of this doctoral research was to update the distribution ranges of the medically important Ixodes ticks in Finland, compare the pathogen prevalence of I. ricinus and I. persulcatus, and examine changes in the prevalence of Borrelia burgdorferi sensu lato (Bbsl) antibodies in the Finnish population over a 50-year period. By using a national citizen collection, the distribution of I. ricinus was updated, and for the first time, a comprehensive mapping of I. persulcatus occurrence in Finland was conducted. The results suggested a northward shift in tick distribution. Ixodes ricinus was the dominant species in southern coastal regions, while I. persulcatus proved to be more common than previously assumed, even appearing to dominate in certain areas, especially in north-western coast. Pathogen prevalence and diversity were higher in I. ricinus, yet I. persulcatus had a higher prevalence of Bbsl bacteria and TBE virus, the causative agents of the two most important tick-borne diseases. The highest pathogen prevalence overall was observed in ticks from southern Finland. In addition, this research detected rare and potentially harmful pathogens not previously reported in Finnish ticks. Antibody measurements from four cross-sectional surveys of the Finnish population collected between 1966 and 2017 showed a significant decrease in Bbsl seroprevalence over a 50-year period. Possible explanations include improved diagnostics, effective and prompt antibiotic treatment, increased public awareness, and societal and economic changes. The results of this thesis provide new information about the two medically important tick species occurring in Finland, the pathogens they carry, and changes in Bbsl exposure in the population. Moreover, it highlights the importance of continuous surveillance and public awareness in managing the risks of tick-borne diseases.

----- Puutiaiset ja niiden levittämät taudit ovat kasvava kansanterveydellinen huolenaihe Suomessa ja muualla pohjoismaissa, mikä näkyy Lymen borrelioosin (LB) ja puutiaisaivotulehduksen (TBE) tapausmäärien lisääntymisenä. Vielä vuosikymmen sitten puutiaistutkimus oli vähäistä Suomessa ja viimeinen puutiaisten levinneisyyttä koskeva tutkimus oli julkaistu vuonna 1961. Väitöskirjatyön tavoitteena oli päivittää ihmisille terveydellisesti merkittävien Ixodes-puutiaisten levinneisyysalueet Suomessa, vertailla puutiaisen (I. ricinus) ja siperianpuutiaisen (I. persulcatus) patogeenimääriä sekä tutkia Borrelia burgdorferi sensu lato (Bbsl) -bakteerin vasta-aineiden esiintyvyydessä tapahtuneita muutoksia suomalaisessa väestössä 50 vuoden aikana. Valtakunnallisen kansalaiskeräyksen avulla I. ricinus -puutiaisen levinneisyys päivitettiin, ja ensimmäistä kertaa saatiin kattava kartoitus I. persulcatus -puutiaisen esiintymisestä Suomessa. Tulokset viittasivat puutiaisten levinneisyysalueen siirtyneen pohjoisemmaksi. Ixodes ricinus oli valtalajina eteläisillä rannikkoalueilla, kun taas I. persulcatus oli odotettua yleisempi ja paikoin jopa vallitseva laji tietyillä alueilla, erityisesti luoteisrannikolla. Patogeenien esiintyvyys ja monimuotoisuus olivat suuremmat I. ricinus -puutiaisilla, mutta I. persulcatus -puutiaisilla havaittiin korkeampi esiintyvyys kahden tärkeimmän puutiaistaudinaiheuttajan, Bbsl-bakteerin ja TBE-viruksen osalta. Korkein patogeeniprevalenssi oli eteläisen Suomen puutiaisilla. Lisäksi tutkimus havaitsi harvinaisia ja ihmiselle mahdollisesti haitallisia patogeeneja, joita ei oltu aiemmin raportoitu suomalaisista puutiaisista. Vasta-aineiden määritys neljästä vuosien 1966–2017 aikana kerätystä poikki-leikkausotoksesta suomalaisesta väestöstä osoitti, että Bbsl seroprevalenssi on laskenut merkittävästi väestössä 50 vuoden aikana. Mahdollisia selityksiä ovat diagnostiikan kehittyminen, tehokas ja varhainen antibioottihoito, lisääntynyt tietoisuus sekä yhteiskunnalliset muutokset. Väitöskirjan tulokset toivat uutta tietoa kahdesta Suomessa esiintyvästä ihmisen kannalta merkittävästä puutiaislajista, niiden kantamista taudinaiheuttajista sekä muutoksista väestön Bbsl-altistuksessa. Tutkimus korostaa jatkuvan seurannan ja kansalaistietoisuuden merkitystä puutiaislevitteisten tautien hallinnassa.